2022
DOI: 10.33715/inonusaglik.1155682
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Social Skills of Primary School 1st Grade Children Who Lived Their Early Childhood Period in the Pandemic

Abstract: This research aims to examine the social skills of 6-7 year-old primary school children who have lived through the pandemic process in their early childhood, in terms of family and teacher dimensions. The research was designed with convergent parallel mixed design. The study group consisted of 67 children attending the 1st grade of a primary school in Bursa with the typical case sampling method. The quantitative data of the study were collected from the parents and teachers of the children with the "Preschool … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…The fact that children were not sufficiently present in school contexts and could not be together with their peers during the pandemic may have negatively affected their SEBC. Turkish early childhood teachers observed that children who started school after COVID-19 had difficulties with SEBC, such as communicating with peers, peer bullying, and expressing feelings appropriately (Koç, 2022). Thus, the evidence-based practices of teachers to support social–emotional development may have led to a widening gap between the children in the experimental and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that children were not sufficiently present in school contexts and could not be together with their peers during the pandemic may have negatively affected their SEBC. Turkish early childhood teachers observed that children who started school after COVID-19 had difficulties with SEBC, such as communicating with peers, peer bullying, and expressing feelings appropriately (Koç, 2022). Thus, the evidence-based practices of teachers to support social–emotional development may have led to a widening gap between the children in the experimental and control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Living harmoniously in society as healthy individuals depends on acquiring developmental characteristics and skills during these first 'magical' years of life. In this context, early childhood social-emotional skills development is vital to support children in regulating and managing their social acceptance and emotions in society (Koc, 2022). Social-emotional skills are capable of being imparted and gained through suitable educational methods.…”
Section: Introductionmentioning
confidence: 99%